The Implementation of the Team Assited Individualization Learning Model to Improve Student’s Learning Outcomes - Lidia Rambu Day; Priangga Pratama Putra Haryanto (Gateway for Understanding Research in Education, 2026)
This study aims to examine the effect of the Team Assisted Individualization (TAI) learning model on students’ learning outcomes and analytical thinking skills. The study addresses the limited development of higher-order thinking skills (HOTS), particularly analytical skills (C4), among elementary school students. Although previous studies have shown the effectiveness of the TAI model, its specific impact on analytical skills in science learning remains underexplored. This research employed a quasi-experimental method with a post-test only control group design. The sample consisted of an experimental class and a control class. Data were collected using a validated test instrument and analyzed through normality, homogeneity, and independent samples t-test. The results showed a significant difference between the groups, with a significance value of 0.020 (< 0.05), indicating that the TAI model effectively improves students’ learning outcomes and analytical skills